Back Cover: A Nitrogen‐Doped Carbon Catalyst for Electrochemical CO2 Conversion to CO with High Selectivity and Current Density (ChemSusChem 6/2017). Issue 6 (20th March 2017) - Jhong, Huei‐Ru Molly; Tornow, Claire E.; Smid, Bretislav; Gewirth, Andrew A.; Lyth, Stephen M.; Kenis, Paul J. A.
Abstract : The Back Cover picture shows the electrochemical conversion of carbon dioxide to carbon monoxide and water, over a non‐precious nitrogen‐doped carbon catalyst. More details can be found in the Full Paper by Jhong et al. onpage 1094 in Issue 6, 2017 (DOI:10.1002/cssc.201600843 ).